252 REVISITING RISK FACTORS FOR INTRAVENTRICULAR HEMORRHAGE IN PREMATURE INFANTS. Issue 1 (1st January 2007) - Nathalang, D.; Afghani, B.; Waffarn, F.
Abstract : Background: Previous studies have suggested several risk factors for the development of intraventricular hemorrhage (IVH) in premature infants. However, studies to evaluate independent risk factors using multivariate analysis are very scant. Objective: To determine risk factors associated with development of IVH in premature infants at a tertiary care center using multivariate analysis. Methods: Retrospective cohort study of all infants who were born at < 36 weeks' gestational age at the University of California, Irvine Medical Center between January 1998 and October of 2005 and had head ultrasonography (HUS) within the first 60 days of life. For analysis all risk factors must have occurred before IVH. Cases were those with IVH and controls were those without IVH. Characteristics that were compared included gestational age, birth weight, gender, premature rupture of membranes, eclampsia, placenta abruption, chorioamnionitis, delivery type (vaginal vs cesarean), Apgar scores, metabolic acidosis, ventilator use, respiratory distress syndrome, surfactant use, pneumothorax occurrence, seizures, bacteremia, hypertension or hypotension, use of chest compressions, surgery occurrence, existence of necrotizing enterocolitis, transfusion (packed red blood cells, plasma, platelets, cryoprecipitate, or fresh frozen products), and thrombocytopenia before occurrence of IVH. Results: 211 cases with IVH and 330 controls without IVH were identified. Stepwise logistic regression analysis adjusting for significant variables, such as birth weight and gestational age, revealed that only male gender (OR 1.53, CI 1.026-2.30), thrombocytopenia (OR 2.17, 95% CI 1.34-3.5), and seizures (OR 2.90, CI 1.087-7.72) were associated with the development of IVH. Conclusions: Among premature infants < 36 weeks, male gender, thrombocytopenia, and seizures were risk factors for development of IVH. Larger prospective studies are needed to evaluate the association of these risk factors according to their severity and different grades of IVH.